The IceCube Neutrino Observatory IV: Searches for Dark Matter and Exotic Particles - Collaboration, TI (2011)
Exotic particle searches: WIMPs annihilating in the Sun, in the galactic center, in nearby dwarf galaxies; magnetic monopoles; Submitted papers to the 32nd International Cosmic Ray Conference, Beijing 2011.